PERAN ENDING THE SEXUAL EXPLOITATION OF CHILDREN (ECPAT) DALAM MENANGANI KASUS EKSPLOITASI SEKSUAL KOMERSIAL ANAK (ESKA) DI INDONESIA TAHUN 2017 – 2019 - ", Kirana; Rani, Faisyal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research aims to determine the role of ending the sexual exploitation of children (ECPAT) in handling cases of commercial sexual exploitation of children (CSEC) in Indonesia. In an increasingly modern world and easy transportation around the world makes CSEC cases more complex. The high number of child sexual exploitation cases in Indonesia has caused ECPAT Indonesia, as part of an international organization that focuses on handling child sexual exploitation, to take on the role of carrying out various programs and cases with government and non-government agencies to tackle CSEC problems.This study aims to find out how the role played by ECPAT in dealing with CSEC cases in Indonesia in 2017 – 2019. This study uses the theory of the role of International Organizations and qualitative research methods with library research techniques, namely utilizing secondary data obtained through literature studies that get from various literatures such as books, journals, bulletins, newspapers, annual reports of several related agencies, documents, or other materials that support research.ECPAT in tackling the exploitation of child sexuality has a strategy in carrying out its programs, namely advocacy, network building, and outreach to the community. The roles that have been carried out by ECPAT is conducting research or collecting data related to child exploitation, advocating to the government, training section with related institutions to be better prepared at deal with child sexual exploitation issues, and socialization such as campaigns, workshops, or education through courage. Keywords: Role, ECPAT, Commercial Sexual Exploitation of Children